Screening of Plant-Growth-Promoting Bacterial Isolates from Rhizosphere Soil of Prosopis cineraria from U.A.E. - Neeru Sood; Shreya Padmesh Prajapat; Naushin Sadiq Shaikh; Trupti Gokhale; Sumitha Thushar (Environmental Sciences Proceedings, 2022)
Desert regions occupy 33% of the Earth’s land surface. Despite the harsh climatic conditions, different types of plants and microorganisms have adapted to survive and proliferate in these arid extreme conditions and developed associations. Prosopis cineraria is able to flourish in spite of the harsh climatic conditions of high salinity in the desert soils of the United Arab Emirates (U.A.E.), the present study therefore aimed at isolating, screening and understanding the diversity of microflora associated with the rhizosphere region of Prosopis cineraria grown at 15 ds/m salinity. Eleven morphologically distinct purified isolates from rhizosphere soil were screened for IAA production, phosphate solubilization, antibacterial activity and nitrogen-fixing activity. Four of the isolates exhibited nitrogen-fixing activity, two antibacterial activity and five phosphate-solubilizing activity. The plant-growth-promoting bacterial (PGPB) isolates can be used as appropriate bioinoculants which can then in turn be used for cultivation of other plants in the region.